# The Chinese remainder theorem

The Chinese remainder theorem is a theorem in number theory and modulo arithmetics. As such, it doesn’t come up in regular mathematical lessons very often. It is however well-known to all people who have dabbled in cryptography and implementation of popular cryptographic algorithms and attacks.

I happen to be one of those people, so I spent a good amount of time researching the theorem and implementations. And now you get the summary of what I discovered!

All implementations are going to be in Python. I mostly used this stuff in little scripts here and there, so I never spent the time translating them to anything else.

# The theorem

Let’s consider the following set of k equations:

`x = a1 (mod n1)`

...

x = ak (mod nk)

This is equivalent to saying that `x mod ni = ai`

(for i=1…k). The notation above is common in group theory: you define the group of integers modulo some number n and then you state equivalences (or *congruences*) within that group. Careful not to confuse them with actual equivalences!

Here, x is the unknown; instead of knowing x, we know the remainder of the division of x by a group of numbers. If the numbers ni are pairwise coprimes (i.e. each one is coprime with all the others) then the equations have exactly one solution. Such solution will be modulo N, with N equal to the product of all the ni.

**Notes on the history**: the earliest known statement of the theorem is found in a book written in the 3rd century AD by a Chinese mathematician, named Sunzi

*There are certain things whose number is unknown. If we count them by threes, we have two left over; by fives, we have three left over; and by sevens, two are left over. How many things are there?*

However, we would have to wait about 3 more centuries for another Indian mathematician, Aryabhata, to present the first recursive algorithm able to find a solution. Aryabhata was actually trying to solve Diophantine equations of the first order. But I digress. This is another fascinating topic for another day!

# The proof

There are many ways to prove this theorem. Most of them are directly related to the algorithms we can use to find the solution. I chose the proof that I found more immediate to understand; you will see that in action when I show Gauss’ algorithm.

Let’s define a slightly simpler problem, where we have only two equations.

`x = a1 (mod n1)`

x = a2 (mod n2)

As before, let’s define `N = n1 * n2`

.

Let’s define `p = n1^-1 (mod n2)`

and `q = n2^-1 (mod n1)`

. This is the operation called **modular inverse**, where we find the inverse of a number in the group of all the numbers mod N. If I say that p and n1 are inverse in mod n2, this means that `p * n1 = 1 (mod n2)`

. Such inverse only exists when n1 and n2 are coprimes, and here they are by definition.

Now I claim that a solution y to the set of equations can be expressed as:

`y = a1 * q * n2 + a2 * p * n1 (mod N)`

this is a valid solution because `y = a1 * q * n2 = a1 (mod n1)`

and `y = a2 * p * n1 = a2 (mod n2)`

. This follows from the definition of the modular inverse telling me that `p * n1 = 1 (mod n2)`

and `q * n2 = 1 (mod n1)`

.

This is easily extendible to a generic number of equations, where the final construction of y becomes:

`y = sum(ai * (N / ni) * invmod(N / ni, ni)`

When building p and q before, we used only n1 or only n2; what that generalizes to is the product of all moduli excluding the “current one”: the `N / ni`

above. The rest is unchanged.

So we have a solution: the next step is to prove it is the unique solution. Let’s assume a second solution z exists for the same set of equations. Then `z = a1 (mod n1)`

, which implies that `z - y`

is a multiple of n1, since the remainder of their division by n1 is the same number. By the same reasoning, `z - y`

is also a multiple of n2. But since n1 and n2 are coprimes, then it would also be a multiple of N, or as it is often written:

`z = y (mod N)`

z must be the same as y in the mod N group.

# Algorithm 1: Gauss algorithm

This is easy: it is a direct translation to code of the construction explained above. The n and a parameters are lists with all the related factors in order, and N is the product of the moduli.

defChineseRemainderGauss(n, N, a):

result=0foriinrange(len(n)):

ai=a[i]

ni=n[i]

bi=N//ni result+=ai*bi*invmod(bi, ni)returnresult%N

The good thing about this algorithm is that the result is guaranteed to be positive, given bi and ni both positive. This does not apply to the next implementation.

For an implementation of `invmod`

(finding the modular inverse), see next section.

# Algorithm 2: Euclid

This is the *direct construction* procedure described by Wikipedia.

The extended Euclidean algorithm is used to find two coefficients a and b such that `a * (N / ni) + b * ni = gcd(N / ni, ni) = 1`

.

Then x is computed the following way:

`x = sum(ai * b * (N / ni)) for i=1...k`

Translated into code:

defChineseRemainderEuclid(n, N, a):

result=0foriinrange(len(n)):

ai=a[i]

ni=n[i] _, _, si=ExtendedEuclid(ni, N//ni)

result+=ai*si*(N//ni)returnLeastPositiveEquivalent(result, N)

As you can see for my specific application, I wanted only positive results; but the si coefficients can be negative in a lot of cases, making the final sum negative. What do I do in that case? What I did there is to multiply the result by -1, then add N and take the remainder of the division by N, to wrap around the modulus of the solution.

# The extended Euclidean algorithm

As explained above, the algorithm takes two numbers, x and y, and returns two coefficients a and b such that:

`a * x + b * y = gcd(a, b)`

The implementation returns both the coefficients and the GCD itself.

Now if I take two positive integers x and y, I know I can express them as

`x = qy + r`

where q is the *quotient* of the division (i.e. `q = x // y`

where // denotes the integer division) and r is the *remainder* and is always strictly smaller than y. If x is a multiple or y, of course r is going to be zero.

The GCD of two integers can be found by repeating this procedure until the remainder is 0; more specifically:

`x = q1 * y + r1`

q1 = q2 * r + r2

...

The final r before getting to 0 is the GCD. Let’s see this with an example:

gcd(102, 38)102 = 2*38 + 26

38 = 1*26 + 12

26 = 2*12 + 2

12 = 6*2 + 0

so the GCD is 2. Now to find the coefficients we work backwards from the second-to-last division, expressing the new remainder in terms of the other parts:

`2 = 26 - 2*12`

2 = 26 - 2*(38 - 1*26) = 26 - 2*(38 - 1*(102 - 2*38))

2 = 3*102 - 8*38

3 and -8 are the coefficients in the Bezout identity. To compute them in practice we do not work backward, but simply store them as we go, as they can be derived from the main division equation.

defExtendedEuclid(x, y):

x0, x1, y0, y1=1, 0, 0, 1whiley>0:

q, x, y=math.floor(x/y), y, x%y

x0, x1=x1, x0-q*x1

y0, y1=y1, y0-q*y1returna, x0, y0# gcd and the two coefficients

# The modular inverse

Ok so let’s suppose I want to find

`17*x = 1 (mod 43)`

my unknown x is the **modular inverse** of 17 in mod 43. First we need to verify that gcd(17, 43) is 1, otherwise the inverse does not exist. Once we have done that, we compute the two Bezout coefficients as shown above. If we work that out manually by retracing all the divisions, we get:

Forward:

43 = 17*2 + 9

17 = 9*1 + 8

9 = 8*1 + 1 # <-- my GCD is here, so it is 1Backward:

1 = 9 - 8*1

8 = 17 - 9*1

9 = 43 - 17*2Replacing the first "backward" equation with everything else:

1 = 43 - 17*2 - 17 + 43 - 17*2 = 2*43 - 17*5

So we have expressed this in terms of `a*x + b*y = gcd(x, y)`

: 2 and -5 are our Bezout coefficients. Let’s rewrite the last equation in mod 43.

`2*43 - 5*17 = 1 (mod 43)`

But 2*43 is a multiple of 43 so it is irrelevant here; this leaves us with:

`-5*17 = 1 (mod 43)`

By comparing this with the starting equation in the unknown x, -5 is the inverse we were looking for. However we need a positive result: in this case we can do the same procedure we have done earlier, by changing -5 to 5, then adding 43 and computing the mod 43 to remain in the group. This yields 38.

The code is quite simple:

**def** **invmod**(a, m):

g, x, y **=** ExtendedEuclid(a, m)

**if** g **!=** 1:

**raise** ValueError('modular inverse does not exist')

**else**:

**return** x **%** m

# References

Several websites contributed to me getting to the bottom of this interesting theorem and provided the numerical examples I use above: